Genomic organization and evolutionary dynamics of repetitive sequences in Cathartidae (Aves, Cathartiformes) - Oliveira, Iago Santos de (Universidade Federal de São Carlos, 2026)
In this study, we examined how repetitive DNAs influence chromosomal diversification and genome architecture in New World vultures (Cathartidae), a lineage distinguished by exceptional karyotypic stability (2n = 80). We examined five species and three distinct populations of Coragyps atratus using a combination of low-coverage genome sequencing, satellite DNA and repetitive DNA profiling, and in situ and in silico mapping. We found significant diversity in repeat composition between species and populations despite consistent chromosome structure, primarily due to lineage-specific amplification of transposable elements and satellite DNAs. The repeatome was primarily composed of retroelements, particularly LINEs and LTRs, whereas satellitomes exhibited both conserved and rapidly evolving families. Some satellite DNA groups exhibited population-specific divergence, indicating rapid turnover, whereas others were common across all species. The predominant occurrence of satellite DNAs, evidenced by in situ and in silico mapping, in centromeric and pericentromeric regions suggests their structural role in chromosome organization. However, changes in repeat distribution and abundance occurred without notable chromosomal rearrangements, indicating a disjunction between karyotypic evolution and repeat dynamics. Our findings emphasize the necessity of integrating genomic and cytogenetic methodologies to understand genome evolution, illustrating that repetitive DNA serves as a principal catalyst for genomic diversity in birds and demonstrating that substantial genomic innovation can transpire within conserved chromosomal structures
Organização genômica e dinâmica evolutiva de sequencias repetitivas em Cathartidae (Aves, Cathartiformes)
Keywords: Citogenética; Citogenômica comparativa; DNA satélite; Elementos transponíveis; Repeatoma; CIENCIAS BIOLOGICAS::GENETICA; 4. Educação de Qualidade